SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PEMBANGUNAN DAERAH MENERAPKAN METODE PREFERENCE SELECTION INDEX (PSI) - Siahaan, Martina Klarasia; Mesran, Mesran; Hutabarat, Sumiaty Adelina; Afriany, Joli (STMIK Budi Darma, 2018)
This study aims to determine development priorities in 2018 Kota Medan District covering planning, use and evaluation of village development. This study uses qualitative research, with a case study strategy. The technique of collecting data is done by interviews, observation and documentation. Test the validity of data by triangulating data sources and data collection techniques. Data analysis uses determination techniques through data collection, data reduction, data presentation and conclusion. Evaluations for the Village Fund for 2017 include constraints faced during the implementation of development and allocation of village funds such as a lack of sense of responsibility between village officials in managing village funds, people who care about development are still few, and there is a lack of meetings to deliver information on village fund allocation to the community. The decision support system for determining village development priorities has stages, starting from selecting criteria, aspects to assessments that have been set, decision making difficulties in determining priorities and calculating weights. Related to this, the Preference Selection Index (PSI) method can be used to solve the problem. The results of the process are in the form of village rankings as a recommendation for decision making to choose as suitable occupies the designated fields. The results of the system supplementation, it was concluded that the use of this method can help the process of making prioritization of development, can be studied, quite easy to use, and produce information used.Keywords: Decision Support System, Development Priority, PSI